The hollow fiber diffusion system: A novel method for the in situ survival studies in the aquatic environment. - Loh, Chi Leong. (University of Ottawa (Canada), 1994)
The Hollow Fiber Diffusion (HFD) system is a novel approach for the in situ study of the survival of bacteria and viruses in the aquatic environment. The HFD system employs a tangential flow, hollow fiber cartridge with a large area $(7 \times 10\sp3$ cm$\sp2$) of exchange surfaces for diffusion. When compared with diffusion chambers, the HFD system responded significantly faster and more accurately to changes in pH, Eh, nutrient concentrations and to the presence of disinfectants in the external aqueous environment. The T$\sb$ diffusion of low molecular weight substrates was 0.6 h for the HFD system but was 4.2 h for the diffusion chamber. The rate of diffusion or equilibration could be further improved by increasing the flow rate through the HFD system or reducing the volume of the sample reservoir. The HFD system was compatible with all test bacteria and viruses with the possible exception of tailed coliphages. The inactivation of tailed phages by the HFD system can be reduced or eliminated using a slower flow rate or larger diameter hollow fibers. Tailed coliphage inactivation in the HFD system was not apparent in natural waters. Neither adsorption of microorganisms to the hollow fiber membrane surfaces nor colonization of those surfaces was found to be a significant problem during its use in natural waters. A protocol for the decontamination and reuse of the hollow fiber cartridges using hydrogen peroxide was developed and applied successfully. The results of trials of the HFD system at five field sites suggests that the HFD system permits "real-time" accommodation to changes in the physicochemical parameters of the external aqueous environment which can influence the survival of microorganisms. Differences in the survival of microorganisms in the HFD system and in batch samples were shown. The HFD system demonstrated regrowth of Escherichia coli in the Rideau River which is an eutrophic, temperate river. It also demonstrated a diurnal inactivation pattern for Enterococcus durans with the slower decay of E. durans numbers in the hours of darkness. For the other water sources tested (the Ottawa River, the Kennedy Burnett Stormwater Ponds, the Gombak River and the Kroh River), the general order of survival of test microorganisms was MS-2 coliphage $>$ poliovirus $>$ phage B $>$ E. coli and E. durans. In the Rideau River, the order of survival was E. coli $>$ poliovirus $>$ MS-2 coliphage $>$ E. durans. Surprisingly, there was no significant difference in the survival of microorganisms in the two equatorial rivers compared with the survival of the organisms in the oligotrophic, temperate Ottawa River. The HFD system will be very useful in studying the survival and natural ecology of microorganisms in the aquatic environment. It can be applied to model the behavior of water quality indicators, pathogenic organisms and genetically engineered microorganisms. It also has potential for ecotoxicological studies, monitoring for toxins or pollutants in the environment and for the in-line monitoring of the efficiency of water treatment processes such as chlorination.
Keywords: Biology, Microbiology.